Analisis Pengalaman Pengguna Dalam Menggunakan Learning Management System Di STMIK Primakara - Jemris Obet Beay; A.A. Istri Ita Paramitha; Eka Grana Aristyana Dewi (Primakara University, 2022)
STMIK Primakara Online Learning System (SPADA) is an LMS Learning Management System to carry out an online learning system between lecturers and students by providing classes for each subject in the system so that there is also a discussion of the system so that there is also a discussion of the assignments and there is also campus information related to lectures. exist in the system. This study aims to analyze the STMIK Primakara Online Learning System (SPADA) and find out the experiences of SPADA users. There are usability methods and User Experience Questionnaire (UEQ). Respondents consist of all active students and lecturers who use this system. From the results of the study to get the problem formulation in the introduction where there is still confusion in using SPADA so it is necessary to analyze the system so that it can evaluate improvements.